A cephalometric study of patients with cystic fibrosis - Reitman, A A; Faber, R D (The Journal of the American Dental Association (1939), 1978)
Children with cystic fibrosis have skeletal maturation and epiphyseal anomalies similar to those in children with nutritional problems. However, these patients have been found to have normal somatic development if treatment is begun early. In a group of children with cystic fibrosis undergoing medical treatment, cephalometric measurements compared favorably with those established by normal standards.